Inhibitory effects of rambutan (Nephelium lappaceum l.) leaves ethanolic extract on Methicillin-Resistant Staphylococcus aureus (MRSA) and Streptococcus pyogenes - Rizkita, Leonny Dwi; Ariani, Rizka; Farid, Muhammad; Rastrani, Ardestya; Ramadhania, Widya Aryana; Putri, Ratna Aprillia Eka (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2024)
Antimicrobial resistance poses a global health threat, with Methicillin-Resistant Staphylococcus aureus (MRSA) and Streptococcus pyogenes contributing to the highest mortality rates among Gram-positive pathogens over the last three decades. The search for alternative antimicrobial agents has increasingly concentrated on natural products. Rambutan (Nephelium lappaceum L.), a widely used ethnomedicinal plant in Indonesia, is recognized for its numerous health benefits, including its antimicrobial properties. Despite extensive phytochemical studies on various parts of rambutan, the specific inhibitory effects of its leaf extract against MRSA and S. pyogenes have yet to be explored. This study aimed to evaluate the antimicrobial activity of ethanolic rambutan leaf extract against MRSA and S. pyogenes. The extract was prepared using maceration with 96% ethanol, followed by qualitative phytochemical screening, which confirmed the presence of flavonoids (blackish-blue reaction with FeCl3) and tannins (reddish hue with HCl). Antibacterial activity was assessed by measuring inhibition zones on agar plates and determining the minimum inhibitory concentration (MIC) through UV-vis spectrophotometry. The 100% ethanolic extract demonstrated significant inhibitory effects, with a mean inhibition zone of 14.6 mm against MRSA, outperforming the 5% (p = 0.0004) and 10% (p = 0.0402) concentrations. For S. pyogenes, the 100% extract produced the largest inhibition zone (24 mm), showing superior activity compared to the 5% (p = 0.0005) and 10% (p = 0.0485) concentrations. MIC analysis indicated optimal antimicrobial activity at both 50% and 100% concentrations for the two pathogens. These findings underscore the potential of rambutan leaf extract as a natural antimicrobial agent against resistant Gram-positive bacteria, warranting further investigation into its bioactive compounds and mechanisms of action.